STRUCTURAL AND FUNCTIONAL DISORDERS OF GINGIVAL MICROCIRCULATION IN GENERALIZED PERIODONTITIS - Riznyk, Світлана; Riznyk, Юрій (Actual Problems of Medicine and Pharmacy, 2023)
According to the WHO estimates, severe periodontal disease affects about 19% of the world's adult population, accounting for more than one billion cases worldwide. The main risk factors for periodontal disease are poor oral hygiene and tobacco use. Oral diseases cover a range of diseases and conditions that include dental caries, periodontitis (gum disease), tooth loss, oral cancer, orodental injuries, nomas and birth defects such as cleft lip and palate. The relevance of conducting a study of structural and functional disorders of gingival microcirculation in generalized periodontitis is substantiated. Synchronous changes in indicators of the functional state of the periodontal vessels and the microcirculatory bed are observed in the periodontium. The study of structural and functional parallels of the hemomicrocirculatory channel of the periodontium shows that one of the links of the pathogenetic theory of generalized periodontitis is vascular. This study can be used for effective, targeted, comprehensive treatment of generalized periodontitis during pharmacotherapy using drugs of various clinical and pharmacological, nomenclature and legal, classification and legal groups; study of pharmacoeconomic indicators regarding the availability of medicines to this contingent of patients. It has been proven that ultrastructural changes in the plasmolemma of endotheliocytes, both on the side of the vessel lumen and on the side of the basal membrane, indicate a violation of vascular permeability.